The dimensions of comparative librarianship, de J. Periam Danton; Reader in comparative librarianship, editado por D. J. Foskett - Miranda , Antonio (Revista de Biblioteconomia de Brasília, 1978)
DANTON, J. Periam. The dimensions of comparative librarianship. Chicago: American Library Association, 1973. 184 p. ISBN 0-8389-0154-9. $ 6.95. FOSKETT, D. J. (Ed.). Reader in comparative librarianship. Englewood: Information Handling Services, 1976. 333 p. ISBN 0-910972-61-3 (Reader Series in Librarianship and Information Science, 23)